2019
DOI: 10.3389/fchem.2019.00549
|View full text |Cite
|
Sign up to set email alerts
|

A Naphthalimide-Based Fluorescence “Off-on-Off” Chemosensor for Relay Detection of Al3+ and ClO−

Abstract: A novel Al 3+ chemosensor NPA was designed and synthesized on basis of the mechanism of ICT and CHEF. Upon addition of Al 3+ , the probe NPA displayed a bright green fluorescence under UV radiation and visual color change from yellow to colorless. Spectrum titrations showed that NPA could be recognized as a fluorescent turn-on probe with 10 −8 M detection level. The probe wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Using pure methanol solution as a blank, full-wavelength scanning, the absorbance value under the maximum absorption wavelength was recorded, and the operation was repeated three times. For fluorescence measurements, the test solutions of HAN-monosaccharides (5 μM) were prepared with excitation set at 448 nm, and the excitation and emission slit widths both were 10 nm ( Sun et al, 2019 ). For Fourier transform infrared (FT-IR) analyses, HAN-Glc (2 mg) was mixed with dried potassium bromide (200 mg) to ground and pressed under a vacuum condition by using a Nicolet 5700 FT-IR spectrometer and recorded in the wavelength region of 4,000–400 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Using pure methanol solution as a blank, full-wavelength scanning, the absorbance value under the maximum absorption wavelength was recorded, and the operation was repeated three times. For fluorescence measurements, the test solutions of HAN-monosaccharides (5 μM) were prepared with excitation set at 448 nm, and the excitation and emission slit widths both were 10 nm ( Sun et al, 2019 ). For Fourier transform infrared (FT-IR) analyses, HAN-Glc (2 mg) was mixed with dried potassium bromide (200 mg) to ground and pressed under a vacuum condition by using a Nicolet 5700 FT-IR spectrometer and recorded in the wavelength region of 4,000–400 cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…A mass spectra signal at 465.1056 m/z was attributed to [BHMMP+Al 3+ +C2H5OH+H2O-2H − ] + (calcd: 465.1065), which proved that the stoichiometry of the chelate is 1:1 and revealed that the coordination sphere of Al 3+ was composed of solution components, such as water and ethanol (Figure 5). There was a strong binding affinity of BHMMP with Al 3+ , and the association constants calculated from the results of fluorescence and absorption titration experiments were 3.10 × 10 4 (Figure S2) and 2.55 × 10 3 M −1 (Figure S3), by the Benesi-Hildebrand plot, respectively [57][58][59].…”
Section: Binding Mode Studiedmentioning
confidence: 97%
“…While numerous fluorescent chemosensors for a single analyte have been reported, fluorescent chemosensors that allow the sequential sensing of multiple analytes with great selectivity and sensitivity are still needed [19][20][21] because they are more cost-effective, recyclable and practical [22][23][24]. Several fluorescent sensors have been addressed for consecutive sensing of Al 3+ and several anions [25][26][27][28] or several cations and H 2 PO 4 − [29][30][31]. In addition, Kumar et al reported a fluorescent sensor for sequential sensing of Al 3+ and H 2 PO 4 − /HSO 4 − [32].…”
Section: Introductionmentioning
confidence: 99%